A newly discovered PD-L1 B-cell epitope peptide vaccine (PDL1-Vaxx) exhibits potent immune responses and effective anti-tumor immunity in multiple syngeneic mice models and (synergizes) in combination with a dual HER-2 B-cell vaccine (B-Vaxx). (31st December 2022) - Guo, Linlin; Overholser, Jay; Darby, Heather; Ede, Nicholas J.; Kaumaya, Pravin T.P
ABSTRACT: Blockade of checkpoint receptors with monoclonal antibodies against CTLA-4, PD-1 and PD-L1 has shown great clinical success in several cancer subtypes, yielding unprecedented responses albeit a significant number of patients develop resistance and remain refractory. Both PD-1/PD-L1 and HER-2 signaling pathway inhibitors have limited efficacy and exhibits significant toxicities that limit their use. Ongoing clinical studies support the need for rationale combination of immuno-oncology agents to make a significant impact in the lives of cancer patients. We introduce the development of a novel chimeric PD-L1 B-cell peptide epitope vaccine (amino acid 130–147) linked to a "promiscuous" T cell measles virus fusion (MVF) peptide (MVF-PD-L1(130); PDL1-Vaxx) or linked to tetanus toxoid (TT3) TT3-PD-L1 (130) via a linker (GPSL). These vaccine constructs are highly immunogenic and antigenic in several syngeneic animal models. The PD-L1 vaccines elicited high titers of polyclonal antibodies that inhibit tumor growth in multiple syngeneic cancer models, eliciting antibodies of different subtypes IgG1, IgG2a, IgG2b and IgG3, induced PD-1/PD-L1 blockade, decreased proliferation, induced apoptosis and caused ADCC of tumor cells. The PDL1-Vaxx induces similar inhibition of tumor growth versus the standard anti-mouse PD-L1 antibody in both syngeneic BALB/c and C57BL/6J mouse models. The combination of PDL1-Vaxx with HER-2 vaccine B-Vaxx demonstrated synergistic tumor inhibition in D2F2/E2 carcinoma cell line. The anti-PDL1-Vaxx block PD-1/PD-L1 interaction and significantly prolonged anti-tumor responses in multiple syngeneic tumor models. The combination of HER-2 vaccine (B-Vaxx) with either PDL1-Vaxx or PD1-Vaxx demonstrated synergistic tumor inhibition. PDL1-Vaxx is a promising novel safe checkpoint inhibitor vaccine.